Quantification of Osteon Morphology Using Geometric Histomorphometrics. Issue 2 (19th October 2015) - Dillon, Scott; Cunningham, Craig; Felts, Paul
Abstract: Many histological methods in forensic anthropology utilize combinations of traditional histomorphometric parameters which may not accurately describe the morphology of microstructural features. Here, we report the novel application of a geometric morphometric method suitable when considering structures without anatomically homologous landmarks for the quantification of complete secondary osteon size and morphology. The method is tested for its suitability in the measurement of intact secondary osteons using osteons digitized from transverse femoral diaphyseal sections prepared from two human individuals. The results of methodological testing demonstrate the efficacy of the technique when applied to intact secondary osteons. In providing accurate characterization of micromorphology within the robust mathematical framework of geometric morphometrics, this method may surpass traditional histomorphometric variables currently employed in forensic research and practice. A preliminary study of the intersectional histomorphometric variation within the femoral diaphysis is made using this geometric histomorphometric method to demonstrate its potential.